When doing more requires knowing more: Explaining the intention to seek procedural information about recycling - ROSENTHAL, Sonny (Institutional Knowledge at Singapore Management University, 2020)
This study examines the relationship between the intention to recycle more and the intention to seek procedural information, in this case, information about how to recycle. In contrast to prior research that used information seeking as a predictor of behavior change, this study considers behavioral intention as a predictor of intention to seek information. Regression analysis of survey data from Singapore residents confirms that prediction, explaining 27% of the variance in intention to seek procedural information. Moderation analysis suggests the effect of intention to recycle more is stronger among individuals with low recycling self-efficacy. An alternative analysis suggests the greater the intention to recycle more, the stronger the effect of perceived information insufficiency on the intention to seek information. We discuss these effects in relation to the instrumental utility of information and information avoidance. This research contributes to a growing literature describing the importance of procedural information to support recycling behavior.